Pemaknaan Hidup Survivor Kanker Serviks selama Terapi Pengobatan: Literature Review - Regina Aprilia Roberto; Wahyu Hidayati (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2021)
Introduction: Cervical cancer treatment process proves to make women experiencing emotional distress that brings new problems in life. Women with cervical cancer who undergo treatment suffer affecting all aspects of life that impact on the meaning of life. There is limited literature review regarding life meaning resources and technique used by women with cervical cancer who undergo treatment. The aim of this study is to find out description about the meaningfulness in life of cervical cancer survivor during treatment period based on sources and technique of finding meaning. Methods: This study used literature review method. The literature search engines used are SCOPUS, SINTA and Google Scholar. The inclusion criteria of article were articles in Indonesian or English, containing sources and techniques for finding meaning in abstract, respondents cervical cancer survivor and published from 2011 to 2020. Results: Eleven articles show the existence of meaning in life build upon sources of meaning in life including creative, experimental, attitudinal, and hopeful values. Moreover, there are techniques in seeking meaning involving self-understanding, positive action, familiarity with relationships, deepening the values of the meaning of life and worship. Conclusion: The beginning of treatment process results feelings of meaningless, but efforts to make sense of life remain. Family support and spirituality were found to be the things that give the most meaning for cervical cancer survivors to survive.